Brochure for Mary Seacole exhibit - Carlson, Linda, author; Sanders, Eulanda, author (Colorado State University. Libraries, 2000)
Informational flyer for the exhibition “Understanding History through Appearance: An Analysis of a Black Woman in the 19th Century” held in the Gustafson Gallery from April 30 to October 30, 2000. Includes biography of Mary Seacole, a Black businesswoman in the 19th century, and the research process of Dr. Eulanda A. Sanders.
Keywords: Fashion -- History; Fashion -- Exhibitions